Survival of Young Versus Old Patients With Oral Cavity Squamous Cell Carcinoma: A Meta‐Analysis. (2nd December 2020) - Lee, David S.; Ramirez, Ricardo J.; Lee, Jake J.; Valenzuela, Carla V.; Zevallos, Jose P.; Mazul, Angela L.; Puram, Sidharth V.; Doering, Michelle M.; Pipkorn, Patrik; Jackson, Ryan S.
Abstract : Objective/Hypothesis: To assess whether young patients with oral cavity squamous cell carcinoma (OCSCC) demonstrate worse oncologic outcomes than older patients after definitive therapy. Study Design: Systematic review and meta‐analysis. Methods: A medical librarian composed a search strategy to identify relevant studies in Medline, Embase, Scopus, and other major databases (Prospero registration number CRD42019127974). Inclusion criteria were adults with histologically diagnosed OCSCC that underwent treatment, comparator groups with an age cutoff of 40 years old, and reported survival outcomes. Articles were excluded if they contained patients with oropharyngeal squamous cell carcinoma or patients treated for palliative intent. Overall survival hazard ratios were analyzed with a meta‐analysis. Results: There were 23, 382 patients with OCSCC that were treated with definitive therapy from 22 included studies. The pooled cohort contained 2, 238 (10%) patients ≤40 years of age. Oral tongue was the most common subsite in both the younger (n = 1, 961, 91%) and older (n = 18, 047, 88%) cohorts. The majority of OCSCCs were either T1 or T2, representing 859 (80%) malignancies in younger patients and 8, 126 (77%) malignancies in older patients. A meta‐analysis of nine studies demonstrated that younger patients did not experience worse survival outcomes than older patients (hazard ratio = 0.97, 95% confidence interval = 0.66–1.41). Conclusions: Young adults with OCSCC experienced similar oncologic outcomes as older patients with OCSCC after definitive treatment. Until compelling evidence demonstrates clinically relevant differences between these two cohorts, their approach to management should be similar. Future studies should consider comorbidities and using age 40 as a standard age cutoff to provide more uniform data moving forward. Laryngoscope, 131:1310–1319, 2021